Determinants of parental participation in Family‐centered Care in Juvenile Justice Institutions. Issue 1 (19th June 2018) - Simons, Inge; Mulder, Eva; Breuk, René; Rigter, Henk; van Domburgh, Lieke; Vermeiren, Robert
Abstract: This study assessed if staff members of two juvenile justice institutions in the Netherlands were able to motivate parents to participate in a programme of Family‐centred Care. For research purposes, parents were considered to participate if they (a) attended the family meeting, (b) visited their son during regular visiting hours, and (c) participated in measurements. Study participants were the parents of 139 short‐term detained male adolescents. The family meeting was attended by 47% of the parents, most adolescents (74.1%) were visited at least once by their parents, and 42% of the parents participated in measurements. Several factors influenced the parental participation rate variables, although effect sizes were small. The more parenting problems parents faced, the less likely they were to attend the family meeting. Parents with a job visited their son more often than unemployed parents. Finally, a longer stay of the adolescent and Dutch ethnicity predicted more parental participation in measurements. Our study showed that parental participation is feasible. However, the participation rates in the two years after the first steps of implementation were eligible for improvement. More implementation experience where staff could fully benefit from training and coaching in family‐centred work could substantially increase parental participation rates.